2018
DOI: 10.1111/ene.13579
|View full text |Cite|
|
Sign up to set email alerts
|

Value of clinical features to differentiate refractory epilepsy from mimics: a prospective longitudinal cohort study

Abstract: This prospective cohort study identifies rE mimics who are at high risk of morbidity and mortality. rE starting in adulthood should raise a high suspicion of cardiac syncope. Brain MRI is accurate in differentiating rE from other conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
(55 reference statements)
1
7
0
4
Order By: Relevance
“…The study showed that female sex, high seizure frequencies, shorter disease duration, and multiple or ambiguous semiology as well as prominent depressive and anxiety symptoms are in favor of PNES. The current results were concordant with that of Korucuk and colleagues [20] as well as Labate and colleagues [21] who stated that distinguishing PNES from true epileptic ones may be difficult even to experienced observers which must be suspected in any epileptic case with recurrent paroxysmal behavioral abnormalities. They also stated that the evolution of epilepsy monitoring units or the ability to utilize simultaneous video and long-term EEG recordings may be a key to diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…The study showed that female sex, high seizure frequencies, shorter disease duration, and multiple or ambiguous semiology as well as prominent depressive and anxiety symptoms are in favor of PNES. The current results were concordant with that of Korucuk and colleagues [20] as well as Labate and colleagues [21] who stated that distinguishing PNES from true epileptic ones may be difficult even to experienced observers which must be suspected in any epileptic case with recurrent paroxysmal behavioral abnormalities. They also stated that the evolution of epilepsy monitoring units or the ability to utilize simultaneous video and long-term EEG recordings may be a key to diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…8 Berbagai studi telah melaporkan banyak pasien dengan sinkop kardiak ini telah salah didiagnosis sebagai epilepsi refrakter dan mendapatkan terapi OAE dengan segala resiko efek sampingnya. 5,9 Sebuah studi terhadap pasien yang mendapatkan terapi epilepsi di klinik spesialis melaporkan tingkat kesalahan diagnosis sebesar 26%.10 Studi lain dengan pendekatan komunitas melaporkan bahwa kesalahan diagnosis terjadi sebesar 23%. 11 Pada kedua studi tersebut, didapatkan bahwa sinkop kardiovaskular merupakan keadaan yang paling…”
Section: Diskusiunclassified
“…Gejala seperti kepala ringan atau dizziness, diaporesis, nausea dan penurunan kesadaran berhubungan dengan posisi berdiri yang lama lebih merupakan karakteristik dari sinkop vasovagal. 9 Kecurigaan ke arah sinkop juga diperkuat apabila pasien tidak memiliki riwayat kejang sebelumnya atau bangkitan seperti ini baru pertama kali dialami pada pasien dewasa atau usia tua. 6,8,9 Secara epidemiologi, bangkitan epileptik dengan onset usia dewasa pada umumnya merupakan epilepsi simtomatik dengan dasar patologi otak yang jelas seperti stroke, trauma atau tumor.…”
Section: Laporan Kasusunclassified
See 1 more Smart Citation
“…The CME articles published [] in the March 2018 to August 2018 issues contained the statement ‘This paper is being simultaneously published in European Journal of Neurology and Multiple Sclerosis Journal.’ This statement was erroneous and has been removed from the online versions of the articles.…”
mentioning
confidence: 99%